Discourse and practice new tools for critical discourse analysis - Van Leeuwen, Theo, 1947- (Oxford : Oxford University Press, 2008)
Presenting a new theory of discourse, this book argues that our understanding of texts ultimately rests on our practices and on what we do. It will be welcomed by students and researchers looking for a form of discourse analysis that is explicit and methodical as well as socially and critically relevant.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Critical discourse analysis